2008
DOI: 10.1002/adfm.200800633
|View full text |Cite
|
Sign up to set email alerts
|

Organic Phenolic Configurationally Locked Polyene Single Crystals for Electro‐optic and Terahertz Wave Applications

Abstract: We investigate a configurationally locked polyene (CLP) crystal 2‐(3‐(4‐hydroxystyryl)‐5,5‐dimethylcyclohex‐2‐enylidene)malononitrile (OH1) containing a phenolic electron donor, which also acts as a hydrogen bond donor. The OH1 crystals with orthorhombic space group Pna21 (point group mm2) exhibit large second‐order nonlinear optical figures of merit, high thermal stability and very favorable crystal growth characteristics. Higher solubility in methanol and a larger temperature difference between the melting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
189
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 147 publications
(197 citation statements)
references
References 46 publications
2
189
0
Order By: Relevance
“…Furthermore, a slightly asymmetric charge distribution was calculated between the two cyano groups where the charge transfer seems to tend more toward the −C(2)N (14) group. This can be rationalized by the observation that the N(14) atom acts as a hydrogen-bond acceptor of the primary intermolecular interaction, OH···N, the existence of which has been reported previously; 25 this hydrogen bond will lead to an increase in electronegativity of the −C(2)N(14) group relative to that of the other cyano group. Table 2 also presents net charges for various functional groups of OH1 using two other atomic partitioning methods commonly employed in charge-density studies: the Stockholder and QTAIM methods.…”
Section: (B) Harmonic-oscillator Stabilization Energy (Hose)mentioning
confidence: 74%
See 1 more Smart Citation
“…Furthermore, a slightly asymmetric charge distribution was calculated between the two cyano groups where the charge transfer seems to tend more toward the −C(2)N (14) group. This can be rationalized by the observation that the N(14) atom acts as a hydrogen-bond acceptor of the primary intermolecular interaction, OH···N, the existence of which has been reported previously; 25 this hydrogen bond will lead to an increase in electronegativity of the −C(2)N(14) group relative to that of the other cyano group. Table 2 also presents net charges for various functional groups of OH1 using two other atomic partitioning methods commonly employed in charge-density studies: the Stockholder and QTAIM methods.…”
Section: (B) Harmonic-oscillator Stabilization Energy (Hose)mentioning
confidence: 74%
“…The previous report on the crystal structure of OH1 from room-temperature X-ray diffraction [25][26][27]56 suggested that five intermolecular interactions were present; tentative hydrogen-bond separations were given, although X-rays cannot locate hydrogen accurately. In contrast, the neutron-derived crystal structure of OH1, reported herein, gives an accurate measure of hydrogen positions and so is well suited to hydrogen-bonding characterization.…”
Section: Molecular (Hyper)polarizability Coefficientsmentioning
confidence: 96%
“…Yang et al investigated that hydrogen bonds between the sulfonic oxygen atoms and double-bond hydrogen atoms play a role in crystal packing and chromophores orientation [37]. Especially, Kwon et al proposed [38] a configurationally locked polyene (CLP) crystal 2-(3-(4-hydroxystyryl)-5,5-dimethylcyclohex-2-enylidene)malononitrile (OH1) containing a phenolic electron donor, which also acts as a hydrogen bond donor, which exhibited highly efficient second-harmonic generation at 1907 nm fundamental wavelength. Nagalakshmi et al [39] calculated that the first hyperpolarizability of single crystals of hydroxyethylammonium l-tartrate monohydrate [HEALT] stabilized by a set of intermolecular hydrogen bonds is found to be 4.238 × 10 −30 esu, which is 14.2 times that of urea.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, as a first exploration in this direction, we report herein our study on the micellar version of a Pd-promoted homocoupling process of vinyl-and polyenylsilanes that we had previously shown to be an efficient methodology to synthesize extended stereodefined all-trans polyenes up to eight conjugated double bonds long, by doubling in one step the conjugated system of the starting unsaturated silanes. [9] The significance of polyenes in studies dealing with organic electronics is manifold: conjugated polyenes have been investigated as molecular conductors [10] and switches, [11] optical conductors, [12] optical diodes, [13] and nonlinear optical (NLO) materials. [14] Moreover, due to their well-defined chemical structure and possibility of selective functionalization, they represent valuable model systems for validation of predictions based on theoretical calculations and for developing new concepts in organic electronics.…”
Section: Introductionmentioning
confidence: 99%